Impact of Onshore Terminal Operation of Offshore Oil and Gas Engineering on Surrounding Marine Environment and Suggestions - CAO Baojiu; LI Guancheng; WANG Qiabin; LIU Qin; MU Guizhen; LIANG Juping; HOU Minchi (Renmin Zhujiang)
In order to understand the impact of the onshore terminal operation on the marine ecological environment in surrounding sea areas and provide marine ecological environment protection experience for the development and operation of subsequent offshore oil and gas engineering such as an onshore terminal,this paper analyzed the pollutant treatment,surrounding marine ecological environment,risk prevention measures,and emergency capacity building during the onshore terminal operation of an offshore oil and gas engineering from 2016 to 2021.The results showed that the range of averaged COD and oil content in the sea water around the onshore terminal was 0.91~1.69 mg/L and 0.001~0.027 mg/L,respectively,which were in line with the first class standard of sea water quality.The range of averaged oil content in surface sediment was (20.0~169.7)×10-6,which satisfied the first class standard of marine sediment quality.The range of averaged diversity index of phytoplankton,zooplankton,and zoobenthos was 1.13~3.54,0.19~3.42,and 1.47~3.26,respectively.The marine species were abundant,and the ecological environment quality was fine in general.Estuarine environmental changes may be an important factor inducing the fluctuation of marine communities in monitored sea areas.In addition,systematic and reasonable risk prevention measures and emergency capacity building also guaranteed the safe and healthy production of the onshore terminal.